Does higher learning intensity affect student well-being? Evidence from the National Educational Panel Study - Johanna Sophie Quis (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
Starting in 2004/2005, the German state Baden-Wurttemberg reduced academic track duration from nine to eight years, leaving cumulative instruction time mostly unchanged. I use this change in schooling policy to identify the effect of schooling intensity on student well-being in life and school, perceived stress, mental health indicators and self-efficacy. Using rich data from the National Educational Panel Study (NEPS), estimates show higher strains for girls in terms of stress and mental health than for boys. Unexpectedly, male subjective general well-being slightly increases with the reform. Student well-being in school and self-efficacy remain mostly unchanged.
Keywords: I12; I28; I21; J24; 330; self-efficacy; high school reform; subjective well-being; mental health; stress; NEPS